A vascular-liver chip for sensitive detection of nutraceutical metabolites from human pluripotent stem cell derivatives - Yu, Fang (2021)
Human pluripotent stem cell (hPSC) is a great resource for generating cell derivatives for drug efficiency testing. Metabolites of nutraceuticals can exert anti-inflammatory effects on blood vessels. However, the concentration of nutraceutical metabolites produced in hPSC-derived hepatocytes (hPSC-HEPs) is usually low. To enable the detection of these metabolites under the in vitro environment, we have developed a co-culture model consisting of parallel co-culture chambers and a recirculating microfluidic system with minimum fluid volume, optimal cell culture environment. The model allows cells to be exposed continuously to nutraceutical metabolites. In this perfused culturing model, hPSC-derived endothelial cells and hPSC-HEPs are co-cultured without physical contact. When an anti-inflammatory nutraceutical, quercetin, was administrated to the co-culture, higher levels of quercetin metabolites were detected on-chip compared with static control. We further induced inflammation with Interleukin-1β in the co-culture model and measured interleukin 8 (IL-8) generation. The IL-8 level was suppressed more significantly by quercetin metabolites in the perfusion co-culture, as compared to static culture. This is due to enhanced metabolites production on-chip. This microfluidic co-culture model enables in vitro screening of nutraceuticals using hPSC-derived cells.